2020
DOI: 10.1177/0003489420962136
|View full text |Cite
|
Sign up to set email alerts
|

Early Adverse Events Following Transcervical Hypopharyngeal Diverticulum Surgery

Abstract: Objective: To describe rates of short-term morbidity following transcervical surgical treatment of hypopharyngeal diverticulum (HD) and analyze predictors of adverse events. Methods: The 2005 to 2017 National Surgical Quality Improvement Program database was queried to identify patients diagnosed with HD undergoing open transcervical diverticulectomy. Results: A total of 597 patients with a mean age of 71.4 ± 12.3 years were included. Thirty-day adverse events were experienced by 63 (10.6%) subjects, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Surgical management is the first‐line treatment for symptomatic Zenker diverticulum and is commonly performed through an open, transcervical approach 6,7 . Zenker diverticulectomy (ZD), or excision of the diverticulum, is a popular transcervical technique but has been associated with postoperative complications, including pneumonia, sepsis, recurrent nerve palsy, and fistulas 7–9 . Mortality is rare; however, increased age has been associated with greater risk of mortality following ZD 9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical management is the first‐line treatment for symptomatic Zenker diverticulum and is commonly performed through an open, transcervical approach 6,7 . Zenker diverticulectomy (ZD), or excision of the diverticulum, is a popular transcervical technique but has been associated with postoperative complications, including pneumonia, sepsis, recurrent nerve palsy, and fistulas 7–9 . Mortality is rare; however, increased age has been associated with greater risk of mortality following ZD 9 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Zenker diverticulectomy (ZD), or excision of the diverticulum, is a popular transcervical technique but has been associated with postoperative complications, including pneumonia, sepsis, recurrent nerve palsy, and fistulas. [7][8][9] Mortality is rare; however, increased age has been associated with greater risk of mortality following ZD. 9 While still common, open approach ZD has lost favor to endoscopic ZD due to its greater invasiveness and severity of complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative leaks have been reported in endoscopic diverticulotomy and CPM, and are estimated to occur in 1%–20% of patients treated with open diverticulectomy and CPM 9–12 . A recent review of adverse events in open transcervical ZD repair reported a 1%–2% surgical site infection prevalance 13 . In a large analysis of insurance claims, mediastinitis associated with treatment of ZD occurred in 0.3% of patients undergoing surgical management 7 …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] A recent review of adverse events in open transcervical ZD repair reported a 1%-2% surgical site infection prevalance. 13 In a large analysis of insurance claims, mediastinitis associated with treatment of ZD occurred in 0.3% of patients undergoing surgical management. 7 Among dysphagia surgeons and hospital systems performing these surgeries, significant variability exists regarding appropriate postoperative surgical care, risk assessment, and diet advancement.…”
Section: Introductionmentioning
confidence: 99%